Analisa Perancangan Aplikasi Penggajian Pegawai Berbasis Web pada MTs Menggunakan Metodologi RAD - Alen Dian Pangestuti; Besus Maula Sulthon (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Mts Miftahul Amal is an agency that operates in the education sector. This agency carries out payroll using online banking. However, the calculation is done by calculating the data manually and is also only done by one person, so it is prone to delays in providing salary slips and in calculating attendance fines. This thesis will discuss creating a payroll system that can provide convenience for MTs Miftahul Amal admins in calculating employee monthly salaries. This payroll application was created using the Laravel programming language, using the MySql database management system as the database or data storage and Maven as the project management. The payroll application developed using the RAD method has features such as calculating monthly salary, attendance, taxes, BPJS and creating pay slips. It is hoped that by creating this application the process of calculating payroll, absenteeism (absence from work) and permits will become faster and more accurate so as to minimize errors in calculations.  So that the final result obtained from this researcher is to successfully implement the payroll application at MTS Miftahul Amal so that it becomes an appropriate application and analyzes the effectiveness and efficiency of using the payroll application at MTS Miftahul Amal starting from the beginning of the process of inputting payroll component data to obtaining employee payslips and payroll reports.